2019
DOI: 10.3390/md17120694
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Depolymerized Sulfated Galactans from Marine Red Algae on the Growth and Adhesion of Diarrheagenic Escherichia coli

Abstract: Active polysaccharides as safe and natural polymers against bacterial diarrhea have been reconsidered as an alternative to antibiotics. This work investigated the inhibiting effect of depolymerized sulfated galactans from Eucheuma serra and Gracilaria verrucosa on the growth and adhesion of diarrheagenic enterotoxigenic Escherichia coli (ETEC) K88. Results showed that the sulfated polysaccharides with molecular weight distribution ≤20.0 kDa exhibited antibacterial activity against ETEC K88. A structure–activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Zhang et al (2017) found that the soluble proteins in the E. coli culture increased after treating with polysaccharides from Cordyceps cicadae [ 27 ]. Previous studies also confirmed that the sulfated polysaccharides could cause an increase in nucleic acid levels of the ETEC K88 culture [ 11 , 18 ].…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…Zhang et al (2017) found that the soluble proteins in the E. coli culture increased after treating with polysaccharides from Cordyceps cicadae [ 27 ]. Previous studies also confirmed that the sulfated polysaccharides could cause an increase in nucleic acid levels of the ETEC K88 culture [ 11 , 18 ].…”
Section: Resultssupporting
confidence: 55%
“…After high-temperature and high-pressure treatment, the microstructure of the polysaccharides showed a visible change where the flaky structure was broken into porous flocculent. In previous research, an increase in reducing sugar and a decrease in viscosity were evident after the sulfated polysaccharides were hydrolyzed in high-temperature and high-pressure conditions [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations